US monetary policy is more powerful in low economic growth regimes - Roberto A. De Santis; Tommaso Tornese (European Central Bank (ECB), 2024)
We use nonlinear empirical methods to uncover non-linearities in the propagation of monetary policy shocks. We find that the transmission on output, goods prices and asset prices is stronger in a low growth regime, contrary to the findings of Tenreyro and Thwaites (2016). The impact is stronger on private investment and durables and milder on the consumption of nondurable goods and services. In periods of low growth, a contractionary monetary policy implies lower expected Treasury rates and higher premia along the entire Treasury yield curve. Similarly, the corporate excess bond premium rises and the stock market drops substantially during recessions. We use the monetary policy surprises and their predictors provided by Bauer and Swanson (2023a), and identify an additional predictor, the National Financial Condition Index (NFCI), which is relevant in the nonlinear setting. A Threshold VAR, a Smooth-Transition VAR and nonlinear local projection methods all corroborate the findings.
Keywords: C32; E32; 330; Asset prices; business cycles; monetary policy; non-linearities; TVAR; STVAR; local projections